The growth of white rot fungi in the biodelignification process of sawdust of Sengon - Rahayu, Triastuti; Supriadi, Agus; Ningsih, Ike Warti; Asngad, Aminah; Raharjo, Wahyu Purwo (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
Sengon-wood sawdust (SWD) is the waste generated from the sawmill industry and can be utilized as making ethanol and pulp because the waste contains high fiber. The material is processed through biodelignification by white rot fungi. The purpose of this study was to observe the growth of Phanerochaete chrysosporium (PC) and Trametes versicolor (TV) in the biodelignification process of wood sawdust Sengon with a single culture and mixed culture with the growth of white rot fungi macroscopic (spread of the mycelium, the color powder, texture powder) and microscopic (surface properties and thickness of mycelium) using Flat Digital Microscope and SEM (Scanning Electron Microscope). This research method used a Completely Randomized Design (CRD) with one factor: the type of white rot fungi; J1: Phanerochaete chrysosporium, J2: Trametes versicolor), J3: a mixture of PC + TV, with each 3 repetitions. The results showed that The growth of single-culture Phanerochaete chrysosporium in the process of biodelignification of sengon sawdust (SWD) is best compared to single-culture TV and co-culture PC+TV. The results of this study provide information on the selection of types of fungi that have the potential to release lignin, which facilitates the process of pulping or alcoholic fermentation for biofuels.